2018
DOI: 10.3390/genes9030134
|View full text |Cite
|
Sign up to set email alerts
|

The Unforeseen Non-Coding RNAs in Head and Neck Cancer

Abstract: Previously ignored non-coding RNAs (ncRNAs) have become the subject of many studies. However, there is an imbalance in the amount of consideration that ncRNAs are receiving. Some transcripts such as microRNAs (miRNAs) or small interfering RNAs (siRNAs) have gained much attention, but it is necessary to investigate other “pieces of the RNA puzzle”. These can offer a more complete view over normal and pathological cell behavior. The other ncRNA species are less studied, either due to their recent discovery, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 148 publications
0
19
0
Order By: Relevance
“…Long noncoding RNAs (ncRNAs) are transcripts longer than 200 nucleotides. ncRNAs play critical roles in the development and progression of cancer [4,5]. For instance, numerous studies including our owns have found that dysregulations of miRNAs can drive multiple processes of lung tumorigenesis by regulating cell cycle, apoptosis, and migration [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (ncRNAs) are transcripts longer than 200 nucleotides. ncRNAs play critical roles in the development and progression of cancer [4,5]. For instance, numerous studies including our owns have found that dysregulations of miRNAs can drive multiple processes of lung tumorigenesis by regulating cell cycle, apoptosis, and migration [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Since their discovery, moRNAs have been detected in different organisms [3,[5][6][7][8][9][10], including humans [11][12][13][14][15][16][17]. MoRNAs are characterized by high sequence conservation [18] and have been Novel miRNAs are inferred from the known miRNA complementary sequence projected on the precursor, according to the secondary structure hairpin-like folding.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to RNAi, studies have identified several endogenous small RNA types including endogenous siRNA (endo-siRNA), small noncoding RNAs (miRNAs), and piwi-interacting RNA (piRNA) which has created a wider view of normal and pathological cellular mechanisms [1]. The above types are considered non-coding RNAs (ncRNAs) which describes any RNA that does not encode a protein [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Various preclinical research studies have sought to establish diagnostic, prognostic and therapeutic uses for miRNAs [3]. As a result, downregulated miRNAs in cancer cells are referred to as tumor suppressor miRNAs, while miRNAs that permit the expression of genes involved in cancerous processes are called oncomiRs [1]. siRNAs (with 21-25 nucleotides) are produced from exogenous double stranded (dsRNA); their structure is closely related to that of mature miRNAs.…”
Section: Introductionmentioning
confidence: 99%